Prof. dr. Gregor Krek - Dolenc, Janez (Traditiones (Ljubljana), 2006)
Gregor Krek, the son of a cottager, studied languages instead of theology at the University of Graz, where he received a doctorate in Slavic languahes. He become the first profesor and chair for Slavic philology at today's Institute of Slavic Studies in Graz. His most important work was Einleitung in die slavische Literaturgeschichte (Introduction to the History of Slavic Literature), first published in 1874 and revised in 1887.
Keywords: Krek, Gregor, 1840-1905; biografije